2012
DOI: 10.1016/j.cortex.2011.06.010
|View full text |Cite
|
Sign up to set email alerts
|

The right hemisphere is not unitary in its role in aphasia recovery

Abstract: Neurologists and aphasiologists have debated for over a century whether right hemisphere recruitment facilitates or impedes recovery from aphasia. Here we present a well-characterized patient with sequential left and right hemisphere strokes whose case substantially informs this debate. A 72-year-old woman with chronic nonfluent aphasia was enrolled in a trial of transcranial magnetic stimulation (TMS). She underwent 10 daily sessions of inhibitory TMS to the right pars triangularis. Brain activity was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
117
4
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 151 publications
(130 citation statements)
references
References 39 publications
7
117
4
2
Order By: Relevance
“…By some accounts, the right hemisphere plays a largely compensatory role in the reacquisition of language abilities in persons with aphasia. This is supported by lesion studies that have shown that secondary injury to right perisylvian structures can reverse improvements in language performance experienced by patients with prior left hemisphere lesions (Barlow, 1877;Turkeltaub et al, 2012), as well as by more recent studies that have shown that the integrity of right hemisphere structures is associated with improved language recovery (Xing et al, 2016;Pani et al, 2016). In this issue of RNN, work by Zheng and colleagues (2016) builds upon and extends ideas based on this model.…”
Section: Noninvasive Brain Stimulation (Nibs)supporting
confidence: 49%
See 1 more Smart Citation
“…By some accounts, the right hemisphere plays a largely compensatory role in the reacquisition of language abilities in persons with aphasia. This is supported by lesion studies that have shown that secondary injury to right perisylvian structures can reverse improvements in language performance experienced by patients with prior left hemisphere lesions (Barlow, 1877;Turkeltaub et al, 2012), as well as by more recent studies that have shown that the integrity of right hemisphere structures is associated with improved language recovery (Xing et al, 2016;Pani et al, 2016). In this issue of RNN, work by Zheng and colleagues (2016) builds upon and extends ideas based on this model.…”
Section: Noninvasive Brain Stimulation (Nibs)supporting
confidence: 49%
“…In this special issue of RNN, Heiss (2016) presents PET data demonstrating that inhibitory repetitive TMS (rTMS) of the right inferior frontal gyrus results in both clinical improvement in aphasia and a shift from right to left hemisphere activation. Other work has suggested that the role of the right hemisphere in aphasia recovery is not monolithic, that different patients may employ different language recovery mechanisms, and that multiple recovery mechanisms may even be employed within the same individual (Turkeltaub 2012).…”
Section: Noninvasive Brain Stimulation (Nibs)mentioning
confidence: 99%
“…На этом основано применение инактивации гомоло-гичных речевым зонам левого полушария отделов правого полушария с помощью ТМС у больных с речевыми расстройствами для восстановления функции речи [32,33]. Как считают A. Thiel и соавт.…”
Section: Discussionunclassified
“…En segundo lugar, que una persistencia temporal de la activación funcional de la corteza frontal derecha durante la ejecución en tareas de lenguaje en estadios evolucionados de una afasia impide una mayor recuperación de los déficits lingüísticos. Ello pueda explicarse, probablemente, al dificultar que las áreas lingüísticas del hemisferio izquierdo preservadas puedan implicarse en la reorganización funcional del lenguaje perdido [22][23][24] .…”
Section: Introductionunclassified